Wpływ gięcia na charakterystykę in vitro anodowej warstwy wierzchniej implantowego stopu tytanu Ti6Al4V ELI - Kierzkowska, Agnieszka
The aim of the research work was to evaluate the mechanical and electrochemical properties and the behaviour "in vitro" of the anodic surface layer on the Ti6Al4V ELI alloy, deformed by bending. The evaluation is based on the changes of surface bioactivity and protective properties in the maximum plastic strains zone. In the investigation the specimens of 6mm in diameter were used, which were anodized in H3PO4 solution according to the patent PL 185176. Bending was performed by analogy with intra-surgical procedures applied during shaping of implant rods. The deformed surface layers were characterized by a surface roughness and microhardness
Keywords: warstwa anodowa; in vitro; elektrochemia; gięcie; stop tytanu